“Seguridad hídrica en juntas de agua comunitaria: caso de estudio junta administradora de agua potable “recinto pasaje”, cantón Buena Fe, provincia Los Ríos” - Arriaga Loor, Gabriela Jazmín (2022)
The present study was carried out at the "Recinto Pasaje" Drinking Water Administration Board, Buena Fe canton, Los Ríos Province, with the purpose of evaluating water safety and water quality in the stages of the supply system. A diagnosis was established through direct observation; in addition, an interview was conducted with the operator and 54 user surveys were carried out to obtain citizen perception through the validation of Cronbach's Alpha and Principal Component Analysis. For hazard and risk assessment, water samples were taken during eight visits to the study site to analyze the physicochemical parameters of temperature, pH, STD, salinity, conductivity, DO, hardness, turbidity and BOD, which were analyzed using multiparametric equipment, while phosphate, nitrate, nitrite and chloride were analyzed using chemical kits and coliforms were analyzed using qualitative tests. Characterization made it possible to establish a comparison using INEN 1108, WHO, Ministerial Agreement 097-A and Annex 1 of Book VI of the TULSMA. ICA-NSF and non parametric ANOVA analysis of variance were applied to determine statistical differences. Potential hazards/risks were evaluated using the semi-quantitative method. The perception analysis obtained a higher consideration in organoleptic presences in the water. According to the criteria of the regulations, it was possible to identify that the phosphates, BOD, turbidity and coliforms parameters exceeded the permissible criteria. On the other hand, the NSF index indicated that the water quality is "Regular", significant statistical differences